Complications of modified Blalock-Taussig shunts mimicking pulmonary disease. Issue 4 (1st October 1998) - Coren, M E; Green, C; Yates, R; Bush, A
Abstract : The modified Blalock-Taussig shunt is commonly performed as early palliation in cyanotic congenital heart disease. To highlight unusual diagnostic problems in such patients, two cases are reported in whom shunt complications were initially diagnosed as lobar pneumonia and tuberculosis, respectively. The children, an 8 month old boy and a 3 year old boy, had false aneurysm secondary to infection of the graft and dilatation of the left pulmonary artery caused by blood flow through the shunt, respectively.